Design, analysis and validation of a microstrip patch antenna with enhanced coupling for leaf moisture sensing: an IoT approach - Khan, Muhammad Talha; Lin, Xian Qi; Zhe, Chen; Saboor, Abdus (Frontiers in Physics, 2024)
An innovative IoT-based system utilizing modified slotted microstrip patch antenna is introduced for the precise measurement of leaf moisture content. The system features an antenna design that employs a rectangular slot above the feed point of a rectangular patch antenna with an advanced coupling technique for improved sensitivity. It allows the antenna to achieve resonant frequency at lower levels compared to a conventional patch antenna without slots, while still preserving a compact size. The study evaluates the sensitivity of the modified slotted patch antennas by monitoring variations in the reflection coefficient (S11) with respect to resonant frequency as a leaf sample, called sample under test (SUT) is positioned on the patch. A detailed sensitivity comparison and frequency shift analysis are performed between the conventional and proposed antenna designs. The antenna, fabricated on a 0.8 mm F4B substrate, is designed to resonate within the 2.40 to 3.0 GHz range under unloaded conditions. A parametric analysis focusing on the permittivity of the leaf, which ranges from 20 to 30, is conducted to determine the antennas' sensitivity. Experimental results reveal that the proposed patch antenna's is significantly enhanced, ranging from 0.57 to 1.67 times greater than that of traditional patch antenna for the five samples tested. These findings not only highlight the antenna's increased sensitivity in detecting leaf moisture content but also illustrate the potential of the proposed IoT-based system for real time agricultural monitoring, marking a significant advancement in precision farming practices.